Activities of living of disabled people according to the Roper-Logan- Tierney model of nursing - Gisele Nogueira de Moura; Jennara Candido do Nascimento; Maria Alzete de Lima; Natasha Marques Frota; Vicente Matias Cristino; Joselany Afio Caetano (Rev Rene)
Objective: to identify the activities of living of disabled people by applying the Roper-Logan-Tierney Model of Nursing.Methods: cross-sectional study conducted in private university. The population comprised 13 people with physical andsensory disabilities, who practiced water sports. Data collection occurred through structured script. Results: mostparticipants came from the capital, were male, aged between 19 and 69 years. The most affected activities of living were Maintaining a safe environment, Mobilization, and Sleeping. There were 15 nursing diagnoses related to each activityidentified, in addition to the expected outcomes and interventions. Conclusion: the model of living enabled to identify thegroup’s limitations in carrying out activities of living, constituting a fertile field for nursing actions.